2022
DOI: 10.3389/fmicb.2022.826117
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Lysis-Resistant Bacteria and Archaea in the Polyextreme Environment of Salar de Huasco

Abstract: The production of specialized resting cells is a remarkable strategy developed by several organisms to survive unfavorable environmental conditions. Spores are specialized resting cells that are characterized by low to absent metabolic activity and higher resistance. Spore-like cells are known from multiple groups of bacteria, which can form spores under suboptimal growth conditions (e.g., starvation). In contrast, little is known about the production of specialized resting cells in archaea. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 116 publications
0
9
0
Order By: Relevance
“…At large spatial scales, microorganisms are influenced more by dispersal limitation than environmental selection, presumably because microorganisms are not well adapted to disperse over large areas (Chen et al, 2020). In addition to geographical scales, the one‐way flow of rivers limits the dispersal of microorganisms, which is mainly reflected in difficulty moving from downstream to upstream (Chen et al, 2019; Ramírez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At large spatial scales, microorganisms are influenced more by dispersal limitation than environmental selection, presumably because microorganisms are not well adapted to disperse over large areas (Chen et al, 2020). In addition to geographical scales, the one‐way flow of rivers limits the dispersal of microorganisms, which is mainly reflected in difficulty moving from downstream to upstream (Chen et al, 2019; Ramírez et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Archaea have more in common with eukaryotic microbes than bacteria, because bacteria lack certain characteristics such as the presence of histones, complex RNA polymerases and methionine translation initiation (Baker et al, 2020). Accordingly, archaea and bacteria have major differences in their membrane structures, metabolic capacities, dormancy abilities, environmental sensitivities and substrate‐use modes (Baker et al, 2010; Bang & Schmitz, 2018; Ramírez et al, 2022; Santonja et al, 2018; Wei et al, 2020). Thanks to advances in sequencing technology, it is now feasible to conduct highly detailed surveys of microbial communities and explore geographical distributions of microorganisms (Trouche et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, by calculating a lysis-resistant enrichment index of each ASV (including those unclassified), the existence of a fungal seed bank distinct from the lysis prone fraction (considered to be active vegetative cells) was evaluated. The enrichment index showed that, as in the case of Bacteria [32], most ASVs were either enriched in the lysis-resistant fraction or in the total community, with only a small proportion of them showing equal abundance in both fractions.…”
Section: Lysis-resistance In Fungimentioning
confidence: 94%
“…A similar enrichment of intracellular bacteria was found after the application of the lysis-resistant enrichment method. The phyla Tenericutes and Chlamydiae, which are composed of intracellular pathogens [68,69], were enriched in the lysis-resistant fraction [32].…”
Section: Lysis-resistance In Fungimentioning
confidence: 99%
See 1 more Smart Citation